SIM: a secure IP protocol for MANET - Rong-sen LI; Wen-hua DOU (Tongxin xuebao)
According to the core logic of IP Sec, a secure IP protocol was proposed for Mobile Ad Hoc network. Security deal to the packets in and out of the network protocol stack was done by adding a transparent secure layer between trans-port-layer and link-layer. By simplifying the complex security association to simple security association, SIM reduces the cost of initial IP protocol while keeping security. At last a prototype of the proposed protocol was also implemented.